IMPROVING THE EFFICIENCY OF THE STATE CIVIL SERVANTS IN THE ACEH GOVERNMENT HEALTH SERVICE DURING THE PANDEMIC PERIOD - Munawar Ibrahim, Abdul Rahman Lubis, Nurdasila, Hafasnuddin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study explores variables that can influence the performance of the Aceh Government Health Service’s State Civil Servants, namely psychological contract defaults, exchanges of leader-subordinates, and policies. This analysis is quantitative, using primary data collected by distributing questionnaires in 23 districts/cities across Aceh to 290 civil servants on duty. The results of the study confirm previous studies and show that during the Covid-19 pandemic, the performance of the State Civil Servants in the Aceh Health Service can be enhanced by considering factors of psychological contract default, exchanges of leadership-subordinate, and policies.